Fabrication, characterization, and in vitro evaluation of electrospun polyurethane‐gelatin‐carbon nanotube scaffolds for cardiovascular tissue engineering applications. Issue 5 (22nd January 2020) - Tondnevis, Farbod; Keshvari, Hamid; Mohandesi, Jamshid Aghazadeh
Abstract: Myocardial infarction occurs because coronary arteries insufficiency is one of the major causes of mortality worldwide. Recent studies have shown that tissue engineering of myocardial tissue to regenerate infarcted tissue or engineering of the coronary artery may help overcome this problem. In the present research, gelatin and single‐walled carbon nanotube were firstly administrated to physico‐chemically and biologically modulate polyurethane nanofibers. Electrospinning, as versatile and effective technique for production of functional nanoscale fiber, was applied. Incorporation of both gelatin and SWNTs reduced mean diameter of nanofibrous scaffolds from 210 to 140 nm, which influenced on initial cell behavior. Possible interaction between gelatin and SWNTs with polyurethane chains was evaluated using FTIR and DSC techniques. Regarding the incorporation of both gelatin and SWNTs, it was found that hydrophilicity of nanofibrous scaffolds dramatically improved. Scaffold degradation profile was adjusted by incorporation of gelatin. Biomimetic mechanical properties of composite scaffolds like normal blood vessel were developed and SWNTs improved the Young modulus and ultimate strength of scaffolds up to 16.47 ± 0.5 and 23.73 ± 0.5 MPa, respectively. However, addition of gelatin increased elongation at break due to its softening effect. The incorporation of the SWNTs led to significant enhancement of electrical conductivity of the scaffolds. Biological evaluation using SEM and MTT assay demonstrated that nanofibrous surface was covered by confluent and dense layer of both myocardial myoblast and endothelial cells after 7 days of culture, which is crucial for cardiovascular tissue engineering. Results verified that the fabricated scaffolds could be effective for cardiovascular tissue engineering.